Pengaruh Pengungkapan Laporan Keberlanjutan terhadap Nilai Perusahaan pada Perusahaan Sub Sektor Perbankan yang Terdaftar di BEI Periode 2020-2022 - Aljein Maya Rini (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2025)
The main objective of this study is to analyze how corporate value disclosure affects corporate value in banking sub-sector companies listed on the IDX for the 2020-2022 period. The research method used is quantitative, with a sample of 51 banking sub-sector companies. The results show that economic performance disclosure has a positive effect on the dependent variable, namely corporate value. This shows that economic performance disclosure has an influence on company valuation. While environmental performance disclosure and social performance disclosure have negative effects. This shows that both factors, environmental performance disclosure and social performance disclosure are not points that affect company value. This finding provides insight that although sustainability report disclosure has been stipulated in the law, this is still not a point that greatly influences sustainability reports. The results of this study indicate that only economic performance disclosure has an influence on company value, while environmental performance disclosure and social performance disclosure do not affect company value.